PENGARUH KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS VIII SMP ISLAM AL AZHAR 37 PEKANBARU - Maulidah, Friska; Hambali; Haryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by challenges in the learning process due to differences in student abilities, especially interpersonal intelligence. Initial observations and interviews showed that students with high interpersonal intelligence were more active, communicative, and skilled in group discussions, while those with low intelligence tended to be passive and had difficulty collaborating, resulting in inconsistent learning outcomes in Pancasila Education, which requires interaction. The research question in this study is whether there is an effect of interpersonal intelligence on the learning outcomes of Pancasila Education for eighth-grade students at Al Azhar 37 Islamic Junior High School in Pekanbaru. The purpose of this study is to determine the effect of interpersonal intelligence on student learning outcomes. This study used a quantitative method with a quantitative descriptive approach. The population consisted of 77 eighth-grade students. The sample was determined using a saturated sampling technique. The instrument was a questionnaire distributed to eighth-grade students. Data analysis techniques included prerequisite tests (normality, linearity), F-test, simple linear regression test, and coefficient of determination test. The results of data analysis show that there is a positive and significant effect between interpersonal intelligence and student learning outcomes. The calculated F value is 73.72 > F table of 3.97 and sig. (2-tailed) = 0.000 < 0.05, so the Ha hypothesis is accepted. The coefficient of determination of 49.6% indicates that interpersonal intelligence contributes 49.6% to the variation in learning outcomes. In conclusion, interpersonal intelligence effectively improves the Pancasila Education learning outcomes of eighth-grade students at Al Azhar 37 Islamic Junior High School in Pekanbaru.